Cognitive dysfunctions in occipital lobe epilepsy compared to temporal lobe epilepsy. Issue 2 (22nd September 2015) - Santangelo, Gabriella; Trojano, Luigi; Vitale, Carmine; Improta, Ilaria; Alineri, Irma; Meo, Roberta; Bilo, Leonilda
Abstract : Objective: To compare cognitive profiles of occipital lobe epilepsy (OLE) and temporal lobe epilepsy (TLE) and to investigate whether impairment of visuospatial functions is a specific deficit of OLE. Method: Eighteen patients with OLE, 18 patients with TLE, and 18 controls underwent a neuropsychological battery assessing memory, visuospatial functions, and frontal/executive functions. Results: Multivariate analysis evidenced poorer performance of patients with TLE and patients with OLE relative to controls on tasks assessing verbal and non‐verbal long‐term memory, frontal functions, and visuospatial functions. Patients with OLE had poorer performance than patients with TLE on visuospatial tasks, whereas patients with TLE performed worse than patients with OLE on verbal long‐term memory test. Discriminant analysis identified two canonical discriminant functions: The first explained 53.3% of the variance, and the second explained 46.7% of the variance. The first function included verbal and non‐verbal memory tests distinguishing controls from both OLE and TLE, whereas the second factor including a visuoconstructional test distinguished OLE from TLE and controls. Conclusions: The results demonstrate that visuoconstructional dysfunction is related to OLE and support the idea that alterations of occipito‐parietal stream may be specific to patients with OLE.